High frequency dynamic nuclear polarization: New directions for the 21st century - Griffin, Robert G.; Swager, Timothy M.; Temkin, Richard J. (Journal of magnetic resonance (1997), 2019)
[Display omitted] •We review the current state and future of high frequency dynamic nuclear polarization.•Polarizing agents tailored for experiments at high spinning frequencies are essential.•Microwave sources on the horizon are diodes, klystrons, tunable gyrotrons and amplifiers.•Helium recirculation will enable higher spinning frequencies and lower temperature operation.•High frequency gyroamplifiers will enable pulsed DNP experiments.